Neural Circuitry That Mediates Behavior Governing the Tradeoffs Between Survival and Reproduction in Caenorhabditis elegans - Emmons, Scott W (Integr Comp Biol, 2017)
In all outcrossing sexual species there is a mechanism that brings two parents together. For animals, this reproductive requirement may at times conflict with other needs, such as foraging for food. This tension has been studied using the tiny (1 mm) nematode worm, Caenorhabditis elegans. In a trade off between certainty of survival and possibility of reproduction, the C. elegans male will abandon a food patch lacking mates and explore its environment to find one where mates are present. A quantitative behavioral assay has been used to study the behavioral mechanism of mate searching and nutritional, sexual, and neurohormonal pathways that influence the underlying drive state. Taking advantage of the known connectivity of the C. elegans nervous system, neural pathways have been identified that influence the male’s behavior in the presence of food with and without mates.